Using Graphic Organizers to Improve Students’ Reading Comprehension at Grade XI of SMA N 3 Lubuk Basung - Gustina Gustina; Hermawati Syarif (Postgraduate School, Universitas Negeri Padang, 2020)
The background of this research is the students whose achievement is still under the minimum standard (KKM) of learning success and most of them are unwilling to pay serious attention to the text they are reading. This research aims to solve students’ problems in the learning process especially reading comprehension using a graphic organizers. The method used is classroom action research (CAR). The data were collected through reading tests, observation, field notes, and interviews. The result showed that students’ reading comprehension is improved by using a graphic organizer technique. The average of their reading test in the pre-test is 61, 67, 71.25 is in cycle one and 78.75 is in cycle two. Furthermore, the graphic organizer also gives significant effect such as students are more active and confidence in teaching and learning process and they could comprehend text well.